2021
DOI: 10.3389/fpsyt.2021.645289
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Spatial Foundation of Mind in Breaking Vicious Cycles in Anxiety, Insomnia, and Depression: The Future of Virtual Reality Therapy Applications

Abstract: Mental Illnesses, particularly anxiety, insomnia, and depression often involve vicious cycles which are self-perpetuating and can trap one into a more chronic state. For example in the case of insomnia, sympathetic overactivity, intrusive thoughts, and emotional instability due to sleep loss can perpetuate further sleep loss the next night and so on. In this article, we put forward a perspective on breaking these vicious cycles based on preeminent theories in global and spatial cognition, that the foundation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…In previous studies, researchers reported the prevalence of insomnia varying from 11.8% in Nigeria to 27% in the US and 37% in Italy and France and 31.3% in Pakistan. [14][15][16][17] Staner et al, 14 and Jerath et al, 9 found that the prevalence of chronic insomnia was more frequent in the students of first year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, researchers reported the prevalence of insomnia varying from 11.8% in Nigeria to 27% in the US and 37% in Italy and France and 31.3% in Pakistan. [14][15][16][17] Staner et al, 14 and Jerath et al, 9 found that the prevalence of chronic insomnia was more frequent in the students of first year.…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 1250 was estimated through Epitools epidemiological calculator, while keeping the level of significance as 5%, confidence level as 95% prevalence from previous survey as 30%. 9 Non-probability consecutive sampling technique was used data collection after approval from the Ethical Committee of International Islamic University, Islamabad (Certificate no: 622-FSS/BSEDU/F-17).…”
Section: Methodsmentioning
confidence: 99%
“…The potential use of therapeutic applications of VR is discussed in. 101 These applications employed biofeedback designed along with massive virtual spaces to assist in breaking perpetual cycles of insomnia, anxiety, and depression. The VRs can take the shape of a fantastical cosmic scene, mountain tops, or a night sky.…”
Section: Virtual Reality-based Rehabilitationmentioning
confidence: 99%